greet guys, (hyperbolic not trigonometry) since sinh-1 (x) = ln(x + surd(x^2 +1) ) cosh-1 (x) = ln(x + surd(x^2 -1) ) therefore, prove that sinh-1 (x) = (cosh-1(surd(x^2 +1)) anyone please..
Last edited by vocyber; January 16th 2010 at 10:40 PM. Reason: correct jhevon? got solution?
Follow Math Help Forum on Facebook and Google+
Originally Posted by vocyber greet guys, (hyperbolic not trigonometry) since sinh-1 (x) = ln(x + surd(x^2 +1) ) cosh-1 (x) = ln(x + surd(x^2 -1) ) therefore, prove that sinh-1 (x) = (cosh-1(x))(surd(x^2 +1)) anyone please.. this isn't true. make sure you posted the right problem.
View Tag Cloud